Anti-apolipoprotein A-1 autoantibodies are associated with immunodeficiency and systemic inflammation in HIV patients. Issue 2 (February 2018) - Satta, Nathalie; Pagano, Sabrina; Montecucco, Fabrizio; Gencer, Baris; Mach, François; Kaiser, Laurent; Calmy, Alexandra; Vuilleumier, Nicolas
Highlights: The prevalence of anti-apoA-1 autoantibodies is elevated in HIV patients. Correlation of anti-apoA-1 antibodies with low count of CD4+ copies is found. Correlation of anti-apoA-1 antibodies with high level of HIV RNA is found. Anti-apoA-1 antibodies induced the apoptosis of CD4+ cell line SUPT1. Abstract: Objectives: To determine the existence of autoantibodies against apolipoprotein A-1 (anti-apoA-1 IgG) in HIV patients and explore their association with biological features of HIV infection and different inflammatory biomarkers. We also evaluated their impact on CD4 + lymphocytes survival. Methods: Anti-apoA-1 IgG plasma levels were assessed by ELISA in 237 HIV positive patients from a national prospective cohort with no current lipid-lowering therapy. Results: 58% of patients were found positive for anti-apoA-1 IgG and were associated with lower CD4 + counts, but higher viremia and systemic inflammation. Logistic regression analyses indicated that high anti-apoA-1 IgG levels were associated with a 16-fold increased risk of displaying low CD4 + levels, independent of HIV RNA levels and treatment (adjusted Odds ratio [OR]:16.1, 95% Confidence Interval [95%CI]:1.80–143.6; p = 0.01), and a 6-fold increased risk of having a detectable viremia, independent of antiretroviral treatment (OR:5.47; 95% CI:1.63–18.36; p = 0.006). In vitro, anti-apoA-1 IgG induced dose and time-dependent CD4 + apoptosis that was increased by exposure to HIV RNA. Conclusions: In HIV patients, anti-apoA-1 IgG levels are associated with low CD4+ counts, high viremia and a pro-inflammatory systemic profile. Anti-apoA-1 IgG can promote CD4+ lymphocyte apoptosis via undefined pathways.